Trichloroacetic Acid for localized juvenile spongiotic gingival hyperplasia: A case report with a novel treatment. Issue 2 (August 2018) - Moine, L.; Gilligan, G.
Abstract: Introduction: Localized juvenile spongiotic gingival hyperplasia (LJSGH) was originally described by Darling and Chang as a rare gingival condition which involves youngs and young adults. A high recurrence rate was also described after excision. Aim: The aim of this study is to report a case of a 13-years old male with a gingival mass diagnosed as LJSGH treated with a novel treatment based on topical applications of Trichloroacetic Acid (TA) after a conventional surgical treatment. TA could be a safe alternative and a non-invasive technique to treat lesions associated to LJSGH.